CD4+ T cells confer anxiolytic and antidepressant-like effects, but enhance fear memory processes in Rag2−/− mice. (3rd May 2016) - Clark, Sarah M.; Soroka, Jennifer A.; Song, Chang; Li, Xin; Tonelli, Leonardo H.
Abstract: Accumulating evidence supports a role of T cells in behavioral stress responsiveness. Our laboratory previously reported that lymphocyte deficient Rag2 −/− mice on a BALB/c background display resilience to maladaptive stress responses when compared with immune competent mice in the predator odor exposure (POE) paradigm, while exhibiting similar behavior in a cued fear-conditioning (FC) paradigm. In the present study, Rag2 −/− mice on a C57BL/6 background were assessed in the same behavioral paradigms, as well as additional tests of anxiety and depressive-like behavior. Furthermore, the effects of naïve CD4 +  T cells were evaluated by adoptive transfer of functional cells from nonstressed, wild-type donors to Rag2 −/− mice. Consistent with our prior results, Rag2 −/− mice displayed an attenuated startle response after POE. Nevertheless, reconstitution of Rag2 −/− mice with CD4 +  T cells did not modify startle reactivity. Additionally, in contrast with our previous findings, Rag2 −/− mice showed attenuated fear responses in the FC paradigm compared to wild-type mice and reconstitution with CD4 +  T cells promoted fear learning and memory. Notably, reconstitution with CD4 +  T cells had anxiolytic and antidepressant-like effects in Rag2 −/− mice that had not been previously stressed, but had no effect after POE. Taken together, our results support a role of CD4 +  T cells in emotionality, but also indicate that they may promote fear responses by enhancing learning and memory processes.